Nutritional status among women with preeclampsia and healthy pregnant women - Samur, Gülhan; Akkuş, Özlem Özpak; Ede, Gözde; Ayaz, Aylin; Mutlu, Aslı Akyol; Akkuş, Melih; Danışman, Nuri (Progress in Nutrition, 2016)
Aim: Pregnancy-onset hypertension and proteinuria is defined as preeclampsia (PE). PE affects 2% to 8% of all pregnancies and causes both maternal and perinatal morbidity and mortality. The aim of the present study was to compare the nutritional status of women with PE with healthy pregnant. Methods: This research was carried out at local women health care, education and research hospital in Ankara, Turkey. Thirty pregnant women who were being followed up with the diagnosis of preeclampsia and 30 healthy pregnant women as a control group involved in the study. All participants were given an introduction to the research and a questionnaire regarding their nutritional status and habits. Anthropometric measurements and blood samples were taken. Results: Weight gain during pregnancy, gestational age and fetal birth weight were found to be significantly lower in preeclamptic pregnant women than healthy pregnant women (p<0.001). On the other hand, pre-pregnancy BMI was significantly higher in the preeclamptic group (p<0.001). Women with PE had higher blood pressure, fasting blood glucose concentration, serum total cholesterol, triglyceride and homocystein levels compared to healthy pregnant women (p<0.05). Average daily energy, carbohydrates, fiber, vitamin B6 intakes were significantly different between preeclamptic and healthy pregnant women (p<0.05). There were no statistically significant differences among the groups of the micronutrients except for vitamin B6. Conclusion: Further research that examines the effects of nutritional habits and nutritional supplementation on development of preeclampsia is needed in order to prevent hypertensive disorders in pregnancy.